Evaluating postgraduate preparation in the South African context - Dominguez-Whitehead, Yasmine (Routledge, 2015)
Little work is being undertaken in South Africa to systematically and intentionally prepare undergraduate students to pursue postgraduate studies. This is concerning given the shortage of postgraduate students and the small scale of postgraduate studies. The few programmes and endeavours that exist to prepare students for postgraduate studies are not necessarily evaluated to assess their achievements and shortcomings. This paper provides an evaluation of an academic year-long postgraduate preparation programme, and is specifically concerned with examining subsequent postgraduate enrolment and improvement of participants’ marks. The study draws on both quantitative and qualitative data. The findings indicate that the majority of programme participants proceeded to subsequently enrol in postgraduate studies immediately after completing the programme and that the programme played a role in the pursuit of postgraduate studies. However, the findings also indicate that overall participants’ marks did not improve after participating in the programme. The study brings to light that, while some achievements are possible, the limits of the programme must also be acknowledged.
Keywords: Post-graduate preparation – South Africa